Physical Therapy Management of Functional Constipation in Adults: A 2021 Evidence-Based Clinical Practice Guideline From the American Physical Therapy Association's Academy of Pelvic Health Physical Therapy. Issue 3 (19th July 2022) - LaCross, Jennifer A.; Borello-France, Diane; Marchetti, Gregory F.; Turner, Rose; George, Susan
Abstract : Background: Functional constipation, diagnosed by physicians utilizing the Rome criteria, is a nonpathologic bowel condition resulting in difficulty with defecation. Adults with functional constipation experience infrequent defecation and may strain and/or use manual maneuvers to produce a bowel movement. Physical therapy should be offered as part of conservative intervention. The goals of this guideline were to describe the available evidence and create a reference document of evidence for physical therapists managing adults with functional constipation symptoms. Methods: A systematic search of the literature was performed for articles published between 1990 and 2019 related to physical therapy interventions for adult functional constipation. A summary of details including benefits, risks, harms, and costs related to each intervention category is provided. Results: Strong evidence suggests that physical therapists should offer biofeedback interventions to their patients with functional constipation, including either electromyographic, rectal balloon catheter, or anorectal manometry biofeedback. Moderate evidence supports the use of manual therapy, whereas weak evidence was found to support the use of electrical stimulation to manage adult functional constipation. Finally, although we were not able to grade the evidence for the use of patient education and therapeutic exercise in the physical therapy management of functional constipation, we did provide a summary of these interventions in the literature. Discussion/Conclusions: Our findings suggest that physical therapists can confidently include biofeedback interventions into the plan of care for adults with functional constipation, as they are supported by strong evidence. Manual therapy also provided a degree of evidence suitable to recommend its use.